Hydrogeologic and Hydrochemical Investigation of Aquifers in Semi-rid Area, Central Sudan - Adil, Elkrail; Omer, Kheir; Longcang, Shu; zenchun, Hao (Malaysian Journal of Science, 2003)
The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.The objectives of this paper are to determine the hydraulic properties of the aquifers, construct a piezometric contour map, and to evaluate the chemical characteristics of groundwater with hydrochemical maps of some effective species in Northern Gezira State, Central Sudan. Water head elevations, Jacob and Theis recovery methods and chemical analyses of major constituents were used to achieve these objectives. Transmissivity and the hydraulic conductivity of Gezira aquifer were found to be 368.7 m²/d and 34.03 m/d, respectively, whereas, that of Cretaceous sedimentary aquifer were 407.2 m²/d and 43.17 m/d respectively. Piezometeric contour map confirmed that Blue Nile and White Nile are the main sources of recharge. The upper and lower Gezira aquifers characterized by high concentrations of the physicochemical and chemical species compared to the Cretaceous sedimentary aquifer.